The Unexpected Survival of Employer Collective Action in the United Kingdom - Demougin, Philippe; Gooberman, Leon; Hauptmeier, Marco (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2019)
Recent research within employment relations has identified how employer collective organizations continue to thrive in countries featuring different institutional characteristics. In the UK, we identify 447 membership-based Employer Organizations (EOs) active within employment relations and human resource management. The volume of organizations identified prompts our research question: what explains the changing role and activities of UK EOs?Country-level studies of EOs continuation use a range of theoretical frameworks to analyze how these organizations have adapted to institutional and economic change, but the most effective mode of analysis is debated. Our contribution is to apply Schmitter and Streeck’s identification of logics driving the behaviour of employer collective organizations, previously applied to coordinated market economies as defined by the Varieties of Capitalism framework, to the UK’s liberal market economy. The article explores the extent to which liberalization prompted new behaviour within UK EOs.Some studies argue that EOs in coordinated market economies adapt by prioritizing logics driving influence over those linked to membership. We explore how the UK’s changing political economy spurred evolution in the application of logics and find that the opposite happened. EOs once used participation within collective bargaining agreements and the governance of tripartite bodies to prioritize the logic of influence but these institutions decayed. It might have been expected that such decay would have caused a withering of EOs but they reconstituted themselves instead. The declining salience of the logic of influence prompted employer bodies to focus to a greater degree on the logic of membership by offering a broader range of member-focused services. Our findings indicate that employer collective bodies can react to liberalization with adaptation, not extinction. We also argue that our methodology could shed light on EOs behaviour in North America.